Informal communications as a component of the information and analytical system for ensuring effective business performance - Buhaieva, M.; Zapirchenko, L.; Hrynko, Ya.; Бугаєва, М. В.; Запірченко, Л. Д.; Гринько, Я. В. (Гельветика, 2025)
The article defines the conceptual content of the term “communication”, focusing in particular on various modern forms and types of communication processes that influence business efficiency. It provides definitions and characteristics of both formal and informal communications, substantiating their key role in understanding the dynamics of internal communication processes within a company, especially in the context of their impact on the information and analytical system that ensures effective business operations. Based on the study of leading national and international research, the authors present their own definition of informal communications as processes of information and idea exchange that take place outside of official, structured communication channels. The article offers a more detailed analysis of informal communications, particularly through key questions regarding their significance for business. It is concluded that informal communication plays a crucial role in building flexible and adaptive organizational structures. The paper also identifies and substantiates specific aspects that demonstrate a comprehensive approach to using informal communication as an element of the information and analytical system aimed at enhancing overall business performance. The authors propose defining informal communications, within the framework of an information and analytical system for ensuring effective business operations, as spontaneous processes of information exchange that occur outside official communication channels, enabling fast and flexible transfer of knowledge and ideas within the organization. The article defines the information and analytical support system for effective business activity as a structure that encompasses the collection, analysis, storage, and distribution of information necessary to support operational, tactical, and strategic management decisions. To conduct an in-depth analysis of informal communications within such a system, the authors outline and substantiate specific aspects: the role of informal communication in information collection and exchange, its influence on decision-making and strategies, cultural and social context, technological support, and impact measurement. Based on a comprehensive study, scientifically grounded recommendations have been developed to optimize informal communication within the information and analytical system of business operations, presented by the authors in the form of a generalized model. У статті визначено змістовне наповнення категорії «комунікації», зокрема розглянуті різні сучасні форми та види комунікаційних процесів, які впливають на ефективність бізнесу. Надано визначення і особливості формальних та неформальних комунікацій, обґрунтовано, що вони є ключовими для розуміння динаміки внутрішніх комунікативних процесів у компанії, особливо в контексті їхнього впливу на інформаційно-аналітичну систему забезпечення ефективної діяльності бізнесу. Сформовано авторське визначення неформальних комунікацій як процесів обміну інформацією та ідеями, які відбуваються за межами офіційних, структурованих каналів комунікації. Детально розглянуто неформальні комунікації, зокрема розкрито основні питання в контексті визначення їх значення для бізнесу. Визначено, що ці комунікації мають важливе значення у створенні гнучких та адаптивних організаційних структур. Також визначено та обґрунтовано аспекти, що демонструють комплексний підхід до використання неформальних комунікацій як елемента інформаційно-аналітичної системи, спрямованого на підвищення загальної ефективності діяльності бізнесу. Запропоновано визначати неформальні комунікації як складову інформаційно-аналітичної системи забезпечення ефективної діяльності бізнесу – як процеси обміну інформацією, що відбуваються спонтанно та поза офіційними комунікаційними каналами, забезпечуючи швидку та гнучку передачу знань та ідей усередині організації. Дано визначення системи інформаційно-аналітичного забезпечення ефективної діяльності бізнесу як такої структури, що включає збір, аналіз, збереження та розподіл інформації, необхідної для підтримки операційних, тактичних і стратегічних рішень управління. Для глибокого аналізу неформальних комунікацій у цій системі визначені й обґрунтовані їх специфічні аспекти: роль у зборі та обміні інформацією, вплив на рішення та стратегії, культурний і соціальний контекст, технологічна підтримка, вимірювання впливу. На основі проведеного дослідження розроблено науково обґрунтовані рекомендації щодо оптимізації неформальних комунікацій в межах інформаційно-аналітичної системи забезпечення ефективної діяльності бізнесу, які представлені авторами у вигляді узагальнюючої моделі.
Неформальні комунікації як скадова інформаційно-аналітичної системи забезпечення ефективної діяльності бізнесу
Keywords: communication; formal communication; informal communication; information and analytical system; business efficiency; management processes; corporate culture; комунікація; формальні комунікації; неформальні комунікації; інформаційно-аналітична система; ефективність бізнесу; управлінські процеси; корпоративна культура